Level of satisfaction and disfunctions percieved on the quality of attention in an obstetrical service - Vicuña, Marisol (2002)
Objective: To describe the level of satisfaction and disfunctions perceived on the quality of attention in an obstetrical service. Design: Observational, descriptive, transversal study. Material and methods: Hospitalized patients and accompanying persons, at Lima Hipolito Unanue Hospital. An interview was done at medical discharge to hospitalized patients (n= 66); their accompanying persons (n=34) were interviewed at medical discharge from an obstetrical service, employing a semi-structured questionnaire (modified Servqual). Results: High levels of satisfaction for patient’s attention (86,6% patients and 72,4% family) were found. Though, level of satisfaction for the attention to the accompanying person was significatively less (67,7%, p<0,05). Proportion of users who qualified the service as excellent (24,7%) was above Servqual standards. Ninety-two and one-half per cent of users presented one or more disfunctions. Most frequent patient’s complaints were long waiting time, lack of warmth and comfort deficiencies. Conclusion: Hipolito Unanue Hospital obstetrical services users present high levels of satisfaction along with high percentage of complaints. The intervention process nucleus to improve satisfaction is limited and vulnerable to short term intervention.